Sending out an SOS - the bacterial DNA damage response - Marco A. Lima-Noronha; Douglas L. H. Fonseca; Renatta S. Oliveira; Rúbia R. Freitas; Jung H. Park; Rodrigo S. Galhardo (Genetics and Molecular Biology, 2022)
Abstract The term “SOS response” was first coined by Radman in 1974, in an intellectual effort to put together the data suggestive of a concerted gene expression program in cells undergoing DNA damage. A large amount of information about this cellular response has been collected over the following decades. In this review, we will focus on a few of the relevant aspects about the SOS response: its mechanism of control and the stressors which activate it, the diversity of regulated genes in different species, its role in mutagenesis and evolution including the development of antimicrobial resistance, and its relationship with mobile genetic elements.